Antibodies specific to SARS-CoV-2 proteins N, S and E in COVID-19 patients in the normal population and in historical samples. (24th November 2021) - Szymczak, Aleksander; Jędruchniewicz, Natalia; Torelli, Alessandro; Kaczmarzyk-Radka, Agata; Coluccio, Rosa; Kłak, Marlena; Konieczny, Andrzej; Ferenc, Stanisław; Witkiewicz, Wojciech; Montomoli, Emanuele; Miernikiewicz, Paulina; Bąchor, Remigiusz; et al.
Abstract : Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread globally; recognition of immune responses to this virus will be crucial for coronavirus disease 2019 (COVID-19) control, prevention and treatment. We comprehensively analysed IgG and IgA antibody responses to the SARS-CoV-2 nucleocapsid protein (N), spike protein domain 1 (S1) and envelope protein (E) in: SARS-CoV-2-infected patient, healthy, historical and pre-epidemic samples, including patients' medical, epidemiological and diagnostic data, virus-neutralizing capability and kinetics. N-specific IgG and IgA are the most reliable diagnostic targets for infection. Serum IgG levels correlate to IgA levels. Half a year after infection, anti-N and anti-S1 IgG decreased, but sera preserved virus-inhibitory potency; thus, testing for IgG may underestimate the protective potential of antibodies. Historical and pre-epidemic sera did not inhibit SARS-CoV-2, thus its circulation before the pandemic and a protective role from antibodies pre-induced by other coronaviruses cannot be confirmed by this study